Challenges of Labor Market Development and the Necessity of Remote Work Promotion Policies in the RA - Tiratsvyan, Hayk («Ալվարդ Օհանջանյան Վառլենի»)
Labour market dynamics are a cornerstone of economic development, directly shaping employment levels, wage structures, and overall economic stability. In Armenia, long-standing structural challenges—such as the unequal distribution of job opportunities between the capital and the regions, persistently high youth unemployment, and significant wage polarization—continue to constrain labour market inclusivity and economic growth. Addressing these challenges requires a data-driven approach to understanding labour market trends and identifying policy measures to enhance employment opportunities across all economic sectors. This study presents a comprehensive analysis of Armenia’s labour market trends from 2009 to 2024, focusing on the relationship between unemployment and GDP and the effects of household income on consumption expenditures. Using advanced econometric techniques, including correlation analysis, regression modelling, and time-series analysis, the study provides empirical evidence to support labour market policy recommendations. Աշխատաշուկայի դինամիկան կարևոր նշանակություն ունի տնտեսական զարգացման համար՝ անմիջական ազդեցություն ունենալով զբաղվածության մակարդակի, աշխատավարձերի բաշխման և մակրոտնտեսական կայունության վրա։ ՀՀ-ում շարունակում են պահպանվել կառուցվածքային խնդիրներ, ինչպիսիք են` աշխատատեղերի անհամաչափ բաշխվածությունը մայրաքաղաքի և մարզերի միջև, երիտասարդության զբաղվածության մարտահրավերները և աշխատավարձերի բևեռացումը, որոնք խոչընդոտում են աշխատաշուկայի ներառական զարգացմանը։ Այս հետազոտությունը ներկայացնում է ՀՀ աշխատաշուկայի 2009-2024 թվականների հիմնական միտումների վերլուծությունը, գնահատում է գործազրկության ազդեցությունը ՀՆԱ-ի վրա, ինչպես նաև տնային տնտեսությունների եկամուտների և սպառողական ծախսերի միջև կապը՝ կիրառելով տնտեսամաթեմատիկական մեթոդներ, ներառյալ կոռելյացիոն և ռեգրեսիոն վերլուծությունը։ Динамика рынка труда играет ключевую роль в экономическом развитии, напрямую влияя на уровень занятости, структуру заработных плат и общую экономическую стабильность. В Армении на протяжении многих лет сохраняются структурные проблемы, такие как неравномерное распределение рабочих мест между столицей и регионами, высокий уровень безработицы среди молодежи и значительная поляризация заработных плат, что ограничивает инклюзивное развитие рынка труда и замедляет экономический рост. Для преодоления этих вызовов необходим основанный на данных подход, позволяющий глубже понять тенденции на рынке труда и выработать эффективные меры государственной политики, направленные на повышение занятости. В данном исследовании проводится всесторонний анализ тенденций рынка труда Армении в 2009– 2024 годах, с акцентом на влияние безработицы на ВВП и взаимосвязь между доходами домохозяйств и потребительскими расходами. Для достижения научно обоснованных результатов применяются методы корреляционного и регрессионного анализа, а также анализ временных рядов.
Keywords: Economics